Hubungan Waktu Tunggu Obat dengan Tingkat Kepuasan Pasien di Instalasi Farmasi Rawat Jalan Rumah Sakit Umum (RSU) Sumekar Kabupaten Sumenep - Ardiansyah, Rizal; Azmi N, Syafira (Jurnal Indonesia Sehat, 2023)
Background: The hospital pharmacy installation (IFRS) is a patient-focused pharmaceutical service facility with the aim of improving the patient’s quality of life. IFRS must be able to meet the minimum service standar (SPM). waiting time for drug services and patient statisfaction are two of SPM. Purpose: The aim of this research is to analyze the correlation between the variable waiting time for drug services and patient statisfaction. Method: This research is an analytical observational study with a cross sectional design. The research was conducted at outpatient pharmacy installation at RSU Sumekar, Sumenep during periode July 2023. The research sample wat part of population (patients/families of patients who fille prescriptions at the outpatient pharmacy) taken using purposive sampling methode. Analysis of correlation between two variables using chi-square test. Result: 76 respondents (95%) met the stadar waiting time for drug services. The majority of respondents (98.75%) were statisfied with pharmaceutical services. The result of analysis of correlation between two variables show a p-value of 0.473 (p-value>0.05) Conclusion: There is no significant correlation between the waiting time for drug services variable and patient statisfaction variable.